EVALUASI KUALITAS UDARA KARBON MONOKSIDA AKIBAT LALU LINTAS KENDARAAN BERMOTOR - Anjarsari, Ikhfany; Munfarida, Ida; Setyowati, Rr Diah Nugraheni (Fakultas Teknik Universitas Wisnuwardhana, 2019)
The majority (was approximately about 70%) of the Carbon Monoxide (CO) exposure were derived from transportation sector (Damara, et.al, 2017). CO concentration in the air may be caused by anthropological and meteorological factors such as air temperature. This study analysed air quality, air temperature, number of fuel transportation and its correlation. The air quality parameters were CO concentration and air temperature. This study was a quantitative research. CO concentration and Air temperature were measured by CO Analyzer with air temperature sensor inside it. Fuel Transportation was counted by transportation counter. This research was conducted on Weekdays and Weekends at a different time on 07.00-08.00 am, 12.00-01.00 pm, and 4.00-5.00 pm. The results showed that the highest of CO concentrations and air temperature on 07.00-08.00 am, 12.00-01.00 pm, and 4.00-5.00 pm were 71,002 µg /Nm3 and 35 ºC, 20,613 µg /Nm3 and 37 ºC, and 36,646 µg /Nm3 and 35 ºC respectively. Meanwhile the highest number of fuel transportation were 2,442 units, 1,871 units and 2,050 units. There are two site on area of study with CO concentration was exceed national air quality standards according to PP No. 41 of 1999. The Pearson correlation analysis concluded that there are no correlation between air temperature and CO concentration (α = 0.976). Meanwhile there are a correlation between fuel transportation and CO concentration (α = 0,000).